Complaint Behaviour between Generations and Its Transmissions: An Exploratory Study in Malaysia - Hiram, Ting; Wong, Winnie Poh-Ming; Ernest Cyril, de Run (Canadian Center of Science and Education, 2016)
Despite the abundance of marketing literature on consumer complaint behaviour, little is done to explicate such behaviour from generational perspectives. How the older and younger groups complain, and whether the latter learn or inherit behavioural values from the former remain unknown. Using theories pertinent to complaint behaviour and social learning theory as the basis, the present study aims to look into complaint behaviour between two generations, namely the mothers and the daughters. A qualitative approach using dyad interview was employed in Malaysia to gain insights not only about their respective complaint behaviour but also its similarities and differences simultaneously. Subsequently, five pairs of mothers and daughters were interviewed. All interviews were transcribed and analyzed using content analysis. The findings show that while the mothers would most likely seek redress in person, complain to others verbally and take no action, the daughters tend to seek redress and tell others about it using electronic media. There is apparent similarity in seeking redress and ranting on between the mothers and daughters but the younger generation tends to do it via social media. The study thus serves as a precursor to future investigation on complaint behaviour by different generation cohorts in the same family and the potential transmission of behavioural values between them. Practical implications are provided.